2006
DOI: 10.1590/s0074-02762006000600006
|View full text |Cite
|
Sign up to set email alerts
|

Association of rotavirus viroplasms with microtubules through NSP2 and NSP5

Abstract: Rotavirus replication and virus assembly take place in electrodense spherical structures known as viroplasms whose main components are the viral proteins NSP2 and NSP5. The viroplasms are produced since early times after infection and seem to grow by stepwise addition of viral proteins and by fusion, however, the mechanism of viropIasms formation is unknown. In this study we found that the viroplasms surface colocalized with microtubules, and seem to be caged by a microtubule network. Moreover inhibition of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
7
26
0
4
Order By: Relevance
“…(i) The dNSP2-tubulin interaction requires that NSP2 or another interacting protein in the complex be unphosphorylated. (ii) Tubulin is no longer complexed with vNSP2 despite abundant tubulin surrounding viroplasms in the form of microtubules (19,41,49). We also detected acetylated alpha tubulin associated with dNSP2 from untreated and phosphatase-treated RV-infected cell lysates but not with vNSP2.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…(i) The dNSP2-tubulin interaction requires that NSP2 or another interacting protein in the complex be unphosphorylated. (ii) Tubulin is no longer complexed with vNSP2 despite abundant tubulin surrounding viroplasms in the form of microtubules (19,41,49). We also detected acetylated alpha tubulin associated with dNSP2 from untreated and phosphatase-treated RV-infected cell lysates but not with vNSP2.…”
Section: Discussionmentioning
confidence: 71%
“…Acetylated alpha tubulin is generally associated with stabilized microtubules and is observed surrounding viroplasms (49). Nocodazole treatment of RV-infected cells destabilizes microtubules, and the viroplasms observed in these cells are small and do not fuse into larger viroplasms (41). This suggests that dNSP2, with its associated interacting proteins, binds to microtubules and may traffic associated viroplasmic components to sites of viroplasm assembly.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that VF movement on microtubules plays a role in VF coalescence. Similarly, a recent study showed that both NSP2 and NSP5 associate with cellular microtubules and that nocodazole treatment of rotavirus-infected cells results in small, diffuse viroplasms that do not develop into larger, more perinuclear structures (10). Nonetheless, while some FLS and VLS localize near each other in the cytoplasm (perhaps suggesting the movement of both of them on the same microtubule track), this association with microtubules does not result in coalescence events between NS and EGFP/NSP5.…”
Section: Vol 84 2010 Localization Of Mrv Proteins To Cytoplasmic Scmentioning
confidence: 79%
“…The viral nonstructural NS3 protein can induce formation of motile lipid-derived structures, while reorganization of acetylated MTs that may facilitate replication compartment formation appears to involve the structural viral protein VP1 (52,53). Rotavirus, a double-stranded RNA (dsRNA) virus, forms "viroplasms," which begin as many small structures that coalesce into larger ones in perinuclear regions through interactions between two viral nonstructural proteins, NSP2 and NSP5, with MTs (54,55). Nocodazole blocks the movement and fusion of structures to form viroplasms, which, like norovirus replication complexes, appear to embed in acetylated MTs to maintain structural integrity (55,56).…”
Section: Cytoplasmic Replication: Specialized Compartments Need Mts Toomentioning
confidence: 99%